To add six new species freshwater crustaceans (Cyclopoida, Harpacticoida-Copepoda) to the fauna of inland freshwater zooplankton of Vietnam - Hai, Ho Thanh; Luong, Tran Duc (Academia Journal of Biology, 2014)
Based on analysis of many samples collected from Ca river and other waters belonging to Nghean province, one species of Cyclopoida: Halicyclops aequoreus (Fischer, 1860) and five species of Harpacticoida as Tachidius (Neotachidius) triangularis Shen et Tai, 1963; Elaphoidella coronata (Sars, 1904); Onychocamptus mohammed (Blanchard et Richard, 1891); Enhydrosoma bifurcarostratum Shen et Tai, 1965; and Stenhelia (Delavalia) ornamentalia Shen et Tai, 1965 that are firstly determined. All of these species are described in detail in the paper. Among these five species of Harpacticoid, only one Elaphoidella coronata distributed in mountainous waters, four remain species only distributed in blackish waters of estuarine area. Up to now, 12 species of inland freshwater harpacticoid-copepods are recorded in Vietnam. The amount of species of harpacticoid-copepods determined as above that are sure not enough to compare with the real in nature of Vietnam.